First Molecular Characterization of Leishmania Species Causing Visceral Leishmaniasis among Children in Yemen - Mahdy, Mohammed A. K.; Al-Mekhlafi, Abdulsalam M.; Abdul-Ghani, Rashad; Saif-Ali, Reyadh; Al-Mekhlafi, Hesham M.; Al-Eryani, Samira M.; Lim, Yvonne A. L.; Mahmud, Rohela (Public Library of Science (PLOS), 2016)
Visceral leishmaniasis (VL) is a debilitating, often fatal disease caused by Leishmania donovani complex; however, it is a neglected tropical disease. L. donovani complex comprises two closely related species, L. donovani that is mostly anthroponotic and L. infantum that is zoonotic. Differentiation between these two species is critical due to the differences in their epidemiology and pathology. However, they cannot be differentiated morphologically, and their speciation using isoenzyme-based methods poses a difficult task and may be unreliable. Molecular characterization is now the most reliable method to differentiate between them and to determine their phylogenetic relationships. The present study aims to characterize Leishmania species isolated from bone marrows of Yemeni pediatric patients using sequence analysis of the ribosomal internal transcribed spacer-1 (ITS1) gene. Out of 41 isolates from Giemsa-stained bone marrow smears, 25 isolates were successfully amplified by nested polymerase chain reaction and sequenced in both directions. Phylogenetic analysis using neighbor joining method placed all study isolates in one cluster with L. donovani complex (99% bootstrap). The analysis of ITS1 for microsatellite repeat numbers identified L. infantum in 11 isolates and L. donovani in 14 isolates. These data suggest the possibility of both anthroponotic and zoonotic transmission of VL-causing Leishmania species in Yemen. Exploring the possible animal reservoir hosts is therefore needed for effective control to be achieved.